Network Server Management Based on Virtualization Technology using Proxmox at Diskominfo Bengkayang Regency - Sari, Maya; Nurcahyo, Azriel Christian; P, Noviyanti. (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
Based on research conducted by the author, two server machines at Diskominfo Bengkayang District have poor resources because they use personal computers with specifications not for servers, so they cannot serve clients properly. Besides that, there is no central data storage server for sharing data. The solution to the problem of server resources is to replace it with one unit of PC Server with high specifications and because there are two servers, the method used for this problem is Virtualization Technology. All server machines are built in virtualization technology using Proxmox. Proxmox is open-source software for running Virtual Machine. With proxmox, it can minimize the use of hardware and facilitate maintenance because it uses Web Base Management for its settings and with the construction of a data center server for value data storage and data sharing, will provide convenience in doing work. The benefits of this community service activity are to streamline time and costs in server maintenance and optimal use of resources.